Cross-species transmission of CWD prions. Issue 1 (2nd January 2016) - Kurt, Timothy D.; Sigurdson, Christina J.
ABSTRACT: Prions cause fatal neurodegenerative diseases in humans and animals and can be transmitted zoonotically. Chronic wasting disease (CWD) is a highly transmissible prion disease of wild deer and elk that affects cervids over extensive regions of the United States and Canada. The risk of cross-species CWD transmission has been experimentally evaluated in a wide array of mammals, including non-human primates and mouse models expressing human cellular prion protein. Here we review the determinants of cross-species CWD transmission, and propose a model that may explain a structural barrier for CWD transmission to humans.